Family therapy with Muslims - Daneshpour, Manijeh (Routledge, Taylor & Francis Group, 2017)
Family Therapy with Muslims is the first guide for mental health professionals who work with Muslims in the family therapy setting. The book opens with a section defining the similarities across Muslim cultures, the effects of postcolonialism on Muslims, and typical Muslim family dynamics. The author then devotes a chapter to different models of family therapy and how they can specifically be applied to working with Muslim families.